Terminologia da geologia: um estudo descritivo para a tradução - Pletsch, Úrsula Maria (Universidade do Vale do Rio dos Sinos, 2012)
This work aims at performing a descriptive study of Geology’s terminology through the analysis of the linguistic dimension of two hundred terms extracted from an on-line glossary and the classification of those terms in cognitive categories which demonstrate how the knowledge of this area organizes itself and in which way it is communicated. We believe that, having that information, the translator that during his or her job encounters denominative blanks will have aids to create a translation equivalence that does not differ from the patterns present by the area he or she is dealing with. The research consisted in three stages: formal description of the Geology’s terminology, classification of terms in cognitive categories and, lastly, relations with translation. On the first stage were considered, for the simple terms, characteristics such as grammatical class, presence of prefixes and suffixes, using of greek formants and whether the term is also used in ordinary language. The analysis of the complex terms was held in terms of describing what the main configurations of those terms are. On the second stage of our work, the analyzed terms were classified in eleven different cognitive categories of Geology. Doing so, it was possible for us to describe the formal patterns in each one of those categories. The third and last stage of our work aimed at, through the results obtained in the previous stages, to survey the translation difficulties relating to Geology’s terminology and to offer orientation concerning the equivalence of terms between English and Portuguese languages. The results of our work concerning the formal constitution of the terms shows us that on Geology there is the predominance of simple terms, of a nominal base and complex terms composed by a noun followed by an adjective. In relation to the cognitive categories, it is possible to state that most of our terms designate rocks and minerals, physical configuration or processes. The conclusions we reached after the third stage, which crossed the equivalent terms in English with the results obtained in the previous stage, demonstrate the importance of the translator to know the area he or her is translating both terminologically and cognitively, and never to give up on consulting a specialist, once the most evident translation difficulty occurs in relation to the single suffix used in English to name rocks and minerals, being that each one of those material receive a specific suffix in Portuguese.
Keywords: Terminologia; Termo; Tradução; Categorias cognitivas da geologia; Terminology; Term; Translation; Geology’s cognitive categories; ACCNPQ::Lingüística, Letras e Artes::Lingüística